Innovative Knowledge Management Tool of the Visually Impaired Students’ Mental Health Care for Teachers, Parents and Public Health Personnel - Panvipa Bannakiet; Porntip Keyuranon (Journal of Educational Issues, 2024)
Research on innovative knowledge management tool of the visually impaired students’ mental health care for teachers, parents and public health personnel is an academic investigation for research and development purpose. Knowledge management was employed in the early stage of the investigation. The objectives of this study were comprised of 1) developing an innovation to be used by teachers, parents, and public health personnel to provide support to the visually impaired children; 2) sharing knowledge regarding mental health support of the visually impaired students to vision teachers, parents, and relevant public health personnel; and 3) outlining a number of approaches for mental health support to visually impaired children. This study began with an interview with relevant individuals to identify various issues of innovative development with knowledge management. A knowledge management team was formed with participating blind schools which aimed to measure the knowledge level of each school, to design and develop an innovation, to provide access to the knowledge and to identify methods for knowledge sharing. The innovation was adopted in five schools, where the presentation of the investigation results, and knowledge sharing forums were required. There were three main findings: 1) the innovative knowledge management tool was perceived as a handbook with both regular font and braille codes for teachers, parents, and public health personnel to assist visually impaired children with their mental health. The E1/E2 efficiency score of the handbook was 83.55/82.36 which was higher than the stated requirements; 2) Teachers, parents, and public health personnel received a statistically significant higher mean score of cognitive disabilities in mental health support of visually impaired children after the use of the handbook at the.05 level; and 3) a policy recommendation at school, Education Area Office, and Department of Mental Health served as a guideline of mental health support for children with visual impairment.